A Rare Missense Mutation and a Polymorphism with High Frequency in LDLR Gene among Iranian Patients with Familial Hypercholesterolemia - Masoud Tajamolian; Parisa Kolahdouz; Parvaneh Nikpour; Seyed Khalil Forouzannia; Mohammad Hasan Sheikhha; Ehsan Farashahi Yazd (Advanced Biomedical Research, 2018)
Background: Familial hypercholesterolemia (FH) is a disorder that is inherited by autosomal dominant pattern. The main cause of FH disease is the occurrence of mutations in low-density lipoprotein receptor (LDLR) gene sequence, as well as apolipoprotein B and proprotein convertase subtilisin/kexin type 9 genes, located in the next ranks, respectively. Materials and Methods: Forty-five unrelated Iranian patients with FH were screened using a high-resolution melting (HRM) method for exon 9 along with intron/exon boundaries of LDLR gene. Samples with shift in resultant HRM curves were compared to normal ones, sequenced, and analyzed. Results: Our findings revealed a missense mutation c. 1246C>T and a known variant IVS9-30C>T (rs1003723) that was recognized in 71% of the patients (22%: homozygous and 49%: heterozygous genotypes). In silico analysis, predicted the pathological effect of the c. 1246C>T mutation in LDLR protein structure, but IVS9-30C>T variant had no predicted effect on splice site and branch point function. Conclusion: FH is a hereditary type of hypercholesterolemia that leads to premature cardiovascular disease and atherosclerosis, and early diagnosis is needed. We detected a rare missense mutation (1246C>T) and a common single nucleotide polymorphism (SNP) in the Iranian population. These reports could help in the genetic diagnosis and counseling of FH patients.